Prevalence and aetiologies of anaemia among first trimester pregnant women in Sri Lanka; the need for revisiting the current control strategies - Gayani Shashikala Amarasinghe; Thilini Chanchala Agampodi; Vasana Mendis; Krishanthi Malawanage; Chamila Kappagoda; Suneth Buddhika Agampodi (BMC Pregnancy and Childbirth, 2022)
Abstract Background The Sustainable development goals, which focus strongly on equity, aim to end all forms of malnutrition by 2030. However, a significant cause of intergenerational transfer of malnutrition, anaemia in pregnancy, is still a challenge. It is especially so in the low- and middle-income settings where possible context-specific aetiologies leading to anaemia have been poorly explored. This study explores the prevalence of etiological factors significantly contributing to anaemia in pregnancy in Sri Lanka, a lower-middle-income country with a high prevalence of malnutrition albeit robust public health infrastructure. Methods All first-trimester pregnant women registered in the public maternal care programme in the Anuradhapura district from July to September 2019 were invited to participate in Rajarata Pregnancy Cohort (RaPCo). After a full blood count analysis, high-performance liquid chromatography, peripheral blood film examination, serum B12 and folate levels were performed in anaemic participants, guided by an algorithm based on the red cell indices in the full blood count. In addition, serum ferritin was tested in a random subsample of 213 participants. Anaemic women in this subsample underwent B12 and folate testing. Results Among 3127 participants, 14.4% (95%CI 13.2–15.7, n = 451) were anaemic. Haemoglobin ranged between 7.4 to 19.6 g/dl. 331(10.6%) had mild anaemia. Haemoglobin ≥13 g/dl was observed in 39(12.7%). Microcytic, normochromic-normocytic, hypochromic-normocytic and macrocytic anaemia was observed in 243(54%), 114(25.3%), 80(17.8%) and two (0.4%) of full blood counts in anaemic women, respectively. Microcytic anaemia with a red cell count ≥5 * 106 /μl demonstrated a 100% positive predictive value for minor haemoglobinopathies. Minor hemoglobinopathies were present in at least 23.3%(n = 105) of anaemic pregnant women. Prevalence of iron deficiency, B12 deficiency and Southeast Asian ovalocytosis among the anaemic was 41.9% (95%CI 26.4–59.2), 23.8% (95%CI 10.6–45.1) and 0.9% (95%CI 0.3–2.3%), respectively. Folate deficiency was not observed. Conclusion Even though iron deficiency remains the primary cause, minor hemoglobinopathies, B 12 deficiency and other aetiologies substantially contribute to anaemia in pregnancy in this study population. Public health interventions, including screening for minor hemoglobinopathies and multiple micronutrient supplementation in pregnancy, should be considered in the national programme for areas where these problems have been identified.